2022
DOI: 10.1111/sms.14220
|View full text |Cite
|
Sign up to set email alerts
|

Greater effects by performing a small number of eccentric contractions daily than a larger number of them once a week

Abstract: Our previous study found that one maximal voluntary eccentric contraction (MVC-ECC) performed daily for 5 days a week for 4 weeks increased MVC-ECC, isometric (MVC-ISO), and concentric contraction (MVC-CON) torque of the elbow flexors more than 10%. The present study investigated the effects of six maximal voluntary eccentric contractions on the MVC torques and biceps brachii and brachialis muscle thickness (MT). Thirty-six healthy young adults were placed to one of the three groups (N = 12 per group); the 6 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Two previous studies have reported that a higher training frequency (five sessions per week) may be more favorable than a low training frequency (one session per week) with volumes equated between conditions (Yoshida et al, 2022;Zaroni et al, 2019). Yoshida et al (2022) reported that a high training frequency was more effective in increasing strength than a low frequency in resistance-trained men; however, no statistical differences were observed in muscle thicknesses between the groups.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Two previous studies have reported that a higher training frequency (five sessions per week) may be more favorable than a low training frequency (one session per week) with volumes equated between conditions (Yoshida et al, 2022;Zaroni et al, 2019). Yoshida et al (2022) reported that a high training frequency was more effective in increasing strength than a low frequency in resistance-trained men; however, no statistical differences were observed in muscle thicknesses between the groups.…”
Section: Introductionmentioning
confidence: 94%
“…Importantly the training was composed solely of eccentric actions; hence, it is difficult to generalize these findings to traditional dynamic resistance training protocols (Yoshida et al, 2022). Alternatively, Zaroni et al (2019) There were no between-group differences in muscle strength (1-RM bench press, squat, and seated row) (Zaroni et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…72 Total duration of physical activity-either long single or multiple shorter bouts of activity-is what provides the health benefits. 81 Yoshida et al 82 showed greater effects by performing a small number of contractions daily rather than a larger number of them once a week. Buffey et al, 83 conducted a systematic review and meta-analysis of the literature and reported that frequent short interruptions of prolonged sitting with standing and light intensity walking improved biomarkers of cardiometabolic health.…”
Section: Recommended Level Of Activitymentioning
confidence: 99%